PEMELIHARAAN SUMBER DAYA MANUSIA DALAM MANAJEMEN SDM: TENTANG PERAN, STRATEGI, DAN DAMPAKNYA TERHADAP PRAKTIK PEMELIHARAAN KARYAWAN - Achica Erika; Adelia Chicha N; Rinda Nofiana; Indita Ressa A; Rauly Sijabat (CV. Armas Suan Sejahtera, 2025)
Maintenance of Human Resources (HR) is an important part of human resource management aims to maintain continuity, well-being, and labor productivity. In the course of HR Management, this material includes aspects such as compensation, benefits, work safety, health, industrial relations, and work and personal life balance. Effective maintenance strategy can improve motivation, job satisfaction, and loyalty, while suppressing the attendance and turnover. In addition to focusing on the physical and material aspects, maintenance of HR also pays attention to the psychological and social needs of employees. A successful organization is an organization that is able to treat its human resources as the main asset. In lectures, this material is enriched with theories, case studies, and managerial practices so that students are able to understand and apply the concepts of HR maintenance in the world of work. Thus, HR maintenance is one of the keys in creating a productive, harmonious and sustainable work environment